Digital Competence of Christian Education Teachers in Blended Learning: A Case Study in Southwest Maluku - Franklin Untailawan; Asweres A. F. Termas (Soshum: Jurnal Sosial dan Humaniora, 2025)
This study explores the digital competencies of Christian Education teachers in Tiakur City, located in the Southwest Maluku Regency, with a focus on their ability to implement blended learning. The aim of the research was to assess their current digital skills, identify the challenges they face, and determine effective strategies for integrating technology into teaching. A total of 20 teachers from both junior and senior high school levels participated in the study. Using a mixed-methods approach, the research combined surveys, interviews, and classroom observations. The quantitative data from the surveys were analyzed using both descriptive and inferential statistics to evaluate and compare the levels of digital competence. In contrast, the qualitative data collected through interviews and observations were analyzed thematically to identify common patterns and insights. The findings revealed a wide range of digital competencies among the teachers, with some demonstrating strong skills, while others needed additional support. Key challenges identified in the study included limited access to technology, lack of sufficient training, and insufficient technical support. The research highlighted the critical need for targeted professional development, improved technological infrastructure, and enhanced collaboration to support the successful implementation of blended learning. Ultimately, the study emphasizes that improving digital competence and addressing technological barriers are vital to enhancing the quality of Christian Education in remote regions like Southwest Maluku. Keywords: Digital competence, Christian Education, Blended Learning, Techonoly Integration, Teacher training